PENGARUH PEMBELAJARAN INKUIRI TERHADAP LEVEL BERPIKIR SISWA SMA - Nasir, Nur Indah Ririn Fitriani; Damopolii, Insar; Nunaki, Jan Hendriek (Bioilmi: Jurnal Pendidikan, 2020)
The present research aimed to determine the impact of inquiry-based learning (IBL) models towards students' thinking levels. The sample used in this research was 66 students. Measurement student level of thinking used the SOLO taxonomy rubric consisting of five levels: pre-structural (first level), uni-structural (second level), multi-structural (third level), relational (fourth level), and extended abstract (fifth level). Data analyzed was using the Mann Whitney. The result of our research showed that P < 0.05. It can be concluded that there is an impact of IBL on the student's level of thinking. The research recommendation is improving students' thinking levels; teachers can use IBL as innovative learning.